2007
DOI: 10.1192/bjp.bp.106.033514
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal cognitions as a predictor of psychopathology in adolescents with mild intellectual impairment

Abstract: Difficulties experienced by some young people with mild and borderline intellectual disability are associated with enhanced liability to schizophrenia. Clinical methods can both identify those with this extended phenotype and predict those in whom psychosis will occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 36 publications
1
30
0
1
Order By: Relevance
“…The Edinburgh Co-morbidity study employs the variables that were found to be useful in predicting subsequent illness in the Edinburgh High Risk study of schizophrenia (Miller et al 2002). The Co-morbidity study will determine whether there are young people whose learning needs are in fact due to the early stages of a severe form of schizophrenic illness (Johnstone et al 2007). …”
Section: Participantsmentioning
confidence: 99%
“…The Edinburgh Co-morbidity study employs the variables that were found to be useful in predicting subsequent illness in the Edinburgh High Risk study of schizophrenia (Miller et al 2002). The Co-morbidity study will determine whether there are young people whose learning needs are in fact due to the early stages of a severe form of schizophrenic illness (Johnstone et al 2007). …”
Section: Participantsmentioning
confidence: 99%
“…We recruited 93 mothers of young people aged 13–22 from a much larger study of the mental health of young people within the educational system in Scotland who were considered by their teachers to be performing at an approximate IQ level of between 50 and 80 [28]. The mothers identified for this study were contacted initially by telephone and, if interested, questionnaires were sent with a letter of invitation, a consent form and information sheet.…”
Section: Methodsmentioning
confidence: 99%
“…Data were obtained from an ongoing longitudinal follow‐up study of adolescents with special educational needs – the Edinburgh Study of Comorbidity (ESC), full details of which are discussed elsewhere (Johnstone et al . 2007).…”
Section: Methodsmentioning
confidence: 99%